Flame Transfer Functions of the Lean Burnout Zone of an RQL Combustion Chamber - Dynamic Response to Primary Zone and Mixing Port Velocity Fluctuations. Issue 2 (June 2023) - Renner, Julian; March, Martin; Do, Thuy An; Merk, Moritz; Hirsch, Christoph; Sattelmayer, Thomas
This article describes an experimental investigation of thermoacoustic flame transfer functions of the lean burnout zone of an rich–quench–lean combustion chamber. With spatial separation of the rich primary from the lean secondary dilution zone, the latter is independently examined. The multi-microphone-method was employed to characterize the combustor acoustic velocity response to acoustic forcing coming from the primary zone and the mixing ports. The lean secondary zone is then treated as a pure acoustic 3-port network element connected to a 2-port Rankine-Hugoniot flame element. Focusing only on heat release fluctuations due to velocity fluctuations, the former are described by two linear superimposed flame transfer functions as a function of the velocity fluctuations coming from the primary zone and the mixing ports, respectively. Based on a non-reacting and a reacting measurement the two flame transfer functions could be extracted from the experimental data. Within this research, flame transfer functions from the new acoustical approach are presented and compared with ones measured using chemiluminescence and a photomultiplier tube. It is found that the inverse diffusion flame in the burnout zone reacts to velocity fluctuations from the primary zone in the low frequency range and a clear low pass behavior is observed. The mixing port velocity fluctuations create a more broadband response. In the presented cases, the flame transfer functions calculated from chemiluminescence match those from the acoustic method very well.